PERSEPSI MAHASISWA PRODI PPKn TERHADAP BUDAYA MELAYU RIAU ERA MODERNISASI DI UNIVERSITAS RIAU: penelitian deskriptif - NAMIRA RAMADHANI; Edea Mecca Safitri; Fyka Selima Salsabila; Aruma Ayu Wulandari; Mila Amalia; Raihana Raisa; Aila Novianti; Aditya Rifandi; Haryono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the perceptions of Civics and Citizenship Education PPKn students regarding Riau Malay culture. This study used a descriptive qualitative approach, conducting in-depth interviews for data collection. The results indicate that each student has their own perception of Riau Malay culture in this era of modernization. They consider Riau Malay culture a guideline for behavior, politeness, and religiosity. The results also indicate that they possess knowledge of Malay culture, including language, customs, traditional arts, and so on. Riau Malay culture must be preserved to prevent extinction. According to the students, this preservation is crucial, and they play a significant role in its preservation, starting with promoting culture on social media through creative and engaging content and participating in cultural activities in their local communities. Meanwhile, some students are concerned about the influence of modernization on Riau Malay culture due to the growing influence of foreign cultures within the country. This study concludes that despite facing various challenges, Riau Malay culture remains resilient, and Civics and Citizenship Education PPKn students have the potential to be a pathway to preserving Riau Malay culture amidst these changing times.